Effect of hydrogel rectal spacer on seminal vesicle inter-fraction motion during prostate stereotactic body radiotherapy - Hiroaki Kunogi; Nana Shimoyachi; Itsuko Serizawa; Tatsuya Kamima; Noboru Numao; Junji Yonese; Yasuo Yoshioka (Scientific Reports)
Abstract The study aimed to assess the effect of a rectal spacer on the inter-fraction motion of the seminal vesicles (SV) during prostate stereotactic body radiotherapy (SBRT). Clinical data from 60 consecutive patients (300 fractions) with localized prostate cancer treated with definitive SBRT alone (five fractions), between June 2022 and January 2024 were retrospectively reviewed. Of the 60 patients, 44 had a spacer implanted. The residual displacement of SVs in the cone-beam CT relative to those in the planning CT was compared between with and without spacer. The maximum displacement of the proximal SV in 90% of the patients was also evaluated. Additionally, the relationship between the gel/prostate volume ratio and SV displacement was analyzed. The gel/prostate volume ratio was 30 ± 15%. Proximal SV displacement significantly differed with and without the spacer (2.0 vs. 3.8 mm, P < 0.001). Maximum proximal SV displacement also significantly differed with and without the spacer (3.0 vs. 5.1 mm, P < 0.001). In 90% of patients with the spacer, the maximum proximal SV displacement was within 4 mm. SV displacement did not change according to gel/prostate volume ratio. The spacer can limit inter-fraction motion of SVs. The gel/prostate volume ratio was not clinically significant.